Learning from the Past: A Review of Clinical Trials Targeting Amyloid, Tau and Neuroinflammation in Alzheimer’s Disease - Ceyzériat, Kelly; Zilli, Thomas; Millet, Philippe; Frisoni, Giovanni B.; Garibotto, Valentina; Tournier, Benjamin B. (Current Alzheimer Research, 2020)
Alzheimer’s Disease (AD) is the most common neurodegenerative disease and cause of dementia. Characterized by amyloid plaques and neurofibrillary tangles of hyperphosphorylated Tau, AD pathology has been intensively studied during the last century. After a long series of failed trials of drugs targeting amyloid or Tau deposits, currently, hope lies in the positive results of one Phase III trial, highly debated, and on other ongoing trials. In parallel, some approaches target neuroinflammation, another central feature of AD. Therapeutic strategies are initially evaluated on animal models, in which the various drugs have shown effects on the target (decreasing amyloid, Tau and neuroinflammation) and sometimes on cognitive impairment. However, it is important to keep in mind that rodent models have a less complex brain than humans and that the pathology is generally not fully represented. Although they are indispensable tools in the drug discovery process, results obtained from animal models must be viewed with caution. In this review, we focus on the current status of disease-modifying therapies targeting amyloid, Tau and neuroinflammation with particular attention on the discrepancy between positive preclinical results on animal models and failures in clinical trials.
Keywords: tau